Analysis of Factors Influencing the Success in Implementing Non-Formal Education Programs for MSMEs Actors in Rumah BUMN Samarinda - Mustangin Mustangin; Hepy Tri Winarti; A Ismail Lukman; Muhammad Fauzan Akbar; M Iqbal (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2022)
Abstract: The implementation of non-formal education programs by non-formal educational institutions must have supporting factors and obstacles that affect the implementation process. This study aimed at revealing what factors affect non-formal education implementation. This is qualitative research with the descriptive method. The approach and method were chosen because it is in accordance with the purpose of the study, i.e. to reveal in detail what factors affected the non-formal education process in Rumah BUMN Samarinda (center for state-owned enterprises in Samarinda). The data were collected using the interview technique by digging data from sources or informants, namely Rumah BUMN Samarinda managers, tutors or educators in Rumah BUMN Samarinda, and learning residents. The data were then analyzed in several steps, i.e. data reduction, data presentation, and conclusion withdrawal. The results of the study proved that the factors that affect the implementation of non-formal education programs in Rumah BUMN Samainda are the availability of educators or Tutors of BUMN Samarinda, the interest of MSMEs in Rumah BUMN Samarinda, as well as facilities provided by the managers of Rumah BUMN Samarinda to support the learning process.